If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 2x + 2x = 6 Combine like terms: 2x + 2x = 4x -2 + 4x = 6 Solving -2 + 4x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 6 + 2 4x = 6 + 2 Combine like terms: 6 + 2 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| 2(x-9)=10 | | -6.3+b=-6.7 | | -3(-4-6p)-1=83 | | 6t^2-6t+9t= | | 49=7(t+1) | | 2x-10y+3x^2-10x= | | -4t+1=3t+1-7 | | X^2-8x-21=0 | | x+8+6x=13 | | z^13=-13 | | 9(x-5)=72 | | -5(1-4m)=115 | | -5x^2= | | 3x^2+rx=2 | | 9x^4-7x^6+12x^4+14x^6= | | 12x^2-7x-49=0 | | 2(a-8)+7=5(a+2) | | 3x-1+7x=-111 | | 7r+3r-8=8+2r | | -x=-27 | | 6x/12=2/12 | | 6x-20=3(x+5)+13 | | 4x-3y=14 | | k-40+3k+10+2k+20=180 | | 7e+2=16 | | 6=1-2*n+5 | | ln(x-1)+ln(x-1)=ln(11) | | y-2(3-2y)=2y+9 | | 2(w+6)(w-4)=832 | | 10y-22=29-7y | | x/3-7x/12=2/12 | | -30y+5=-6-10y |